2012
DOI: 10.1095/biolreprod.112.102467
|View full text |Cite
|
Sign up to set email alerts
|

Mono-(2-Ethylhexyl) Phthalate Induces Oxidative Stress and Inhibits Growth of Mouse Ovarian Antral Follicles1

Abstract: Mono-(2-ethylhexyl) phthalate (MEHP) is the active metabolite of the most commonly used plasticizer, di-(2-ethylhexyl) phthalate, and is considered to be a reproductive toxicant. However, little is known about the effects of MEHP on ovarian antral follicles. Thus, the present study tested the hypothesis that MEHP inhibits follicle growth via oxidative stress pathways. The data indicate that MEHP increases reactive oxygen species (ROS) levels and inhibits follicle growth in antral follicles, whereas N-acetylcys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 78 publications
6
52
0
1
Order By: Relevance
“…A decrease in ovarian weight, but no change or an increase in preantral follicle numbers could be explained by the follicles being smaller on average than follicles in control ovaries, with fewer granulosa cells per follicle. This possibility is supported by previous studies indicating that DEHP and its metabolite MEHP inhibit follicle growth [43-45]. …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A decrease in ovarian weight, but no change or an increase in preantral follicle numbers could be explained by the follicles being smaller on average than follicles in control ovaries, with fewer granulosa cells per follicle. This possibility is supported by previous studies indicating that DEHP and its metabolite MEHP inhibit follicle growth [43-45]. …”
Section: Discussionsupporting
confidence: 72%
“…It is likely that DEHP, like other endocrine disrupting chemicals, exhibits non-monotonic dose response curves. Specifically, previous studies have indicated that DEHP has a non-monotonic dose response curve specific to gene expression in cultured mouse antral follicles [44-45]. Further, studies in males have shown non-monotonic responses in terms of testicular and serum testosterone levels and anogenital distance and brain aromatase activity [25, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a major factor that triggers the apoptosis pathway (reviewed in [14]), and endocrine disrupting chemicals have been shown to cause oxidative stress in ovaries [17,30]. Thus, we examined whether BPA treatment affects expression of major antioxidant enzymes ( Sod1 , Cat , Gpx , and Gsr ).…”
Section: Resultsmentioning
confidence: 99%
“…Many endocrine disrupting chemicals have been shown to cause oxidative stress in mouse ovaries [17,30], and germ cell nest breakdown is a process that is associated with apoptosis [40]. Thus, the present study also examined whether the ability of BPA to inhibit germ cell nest breakdown was due to effects on the oxidative stress and apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation